Postsecondary Students' Reactions to Agricultural Documentaries: A Qualitative Analysis - Courtney Meyers; Erica Irlbeck; Kelsey Fletcher (Journal of Applied Communications, 2011)
Prior studies have found that television and movie portrayals of science and agriculture can influence attitudes and opinions toward the featured topic or issue. The prevalence of media in modern society emphasizes the need to better understand the possible impact representations of agriculture in entertainment media have on audience members’ attitudes. The purpose of this study was to explore the influence two agricultural documentaries (Food, Inc. and King Corn) had on students’ perceptions of agriculture. Students enrolled in two agricultural communications classes at a southwest university watched one documentary per class, and through reflective journaling, recorded their thoughts about the documentaries. These journals were then analyzed to determine dominant themes and key quotes. Overall, students stated they were upset and offended by the messages presented and sources used in each documentary. Although some students found both documentaries to contain interesting information, for the most part, they found the films to be one-sided and did not portray an accurate depiction of modern agricultural practices. The use of reflective journaling was effective because it allowed all students to provide their viewpoints in response to the films. It also allowed the students to practice writing response statements as some will work in public relations and may be expected to defend their industry should other negative documentaries about agriculture be produced in the future. Additional research should further examine the effectiveness of reflective journaling and gather student perceptions to other films or television shows that feature agriculture.